Enzyme purification: part B. - Jakoby, William B., 1928-; Wilchek, Meir (Methods in enzymology, 1974)
The critically acclaimed laboratory standard, Methods in Enzymology, is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume has been eagerly awaited, frequently consulted, and praised by researchers and reviewers alike. The series contains much material still relevant today - truly an essential publication for researchers in all fields of life sciences.